Coconut shell-based activated carbon preparation and its adsorption efficacy in reducing BOD from The Real Wastewater from Kitchen Restaurant (RWKR): Characteristics, Sorption Capacity, and Isotherm Model - Yasdi Yasdi; Dhea Ussarvi; Rinaldi Rinaldi; Febri Juita; Shassy Endah Cahyani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Real Wastewater from Kitchen Restaurant (RWKR) contains high concentrations of Biochemical Oxygen Demand (BOD) pollutants to pollute the environment. One of the processing alternatives to reduce BOD is the adsorption method using activated carbon from coconut shells. This study aims to determine coconut shell-activated carbon as an adsorbent for the adsorption of organic matter to reduce BOD in RWKR. The method begins with making adsorbents that are activated with activators on HCl 3 M, NaOH 3 M, and H3PO4 M, then a preliminary adsorption test is carried out to select the best activator on coconut shell activated carbon to reduce BOD in RWKR. Determining the optimum conditions for adsorption was carried out by varying pH 3, 4, 5, 6, 7, and 8. Variation of contact time with a stirring speed of 250 rpm, then determined the isotherm model. The remaining organic matter in the wastewater will be measured using a DO meter based on SNI 6989.72: 2009 concerning the method of testing for biochemical oxygen demand (BOD). The results showed that the appropriate activator for coconut shell activated carbon was H3PO4 3 M with an average percentage value of uptake of 89.690%. The adsorption process's optimum pH is at pH 3 with an absorption percentage value of 88.626%. The optimum contact time is at 10 minutes and the adsorption isotherm model used is the Freundlich isotherm with a regression value of R2 = 0.8864.